Metaphor Depicted in Taylor Swift's Songs - Dea Salsabila; Indah Damayanti; Adelia Puspa (International Journal of Innovation and Education Research, 2025)
A metaphor is a figure of speech or figurative language used to make an indirect comparison between two different things. Metaphors can be found in various media, including song lyrics. This research aims to determine the types of metaphors and their meanings in Taylor Swift's album "The Tortured Poets Department: The Anthology." A qualitative descriptive method with data tabulation as the main instrument was employed. The research steps included downloading the song lyrics, listing all the lyrics in sequence, reading them thoroughly, and then identifying and classifying the metaphors using codes before inserting the metaphors into the instruments. The research object contained all the songs on Taylor Swift's latest album, "The Tortured Poets Department: The Anthology." This study utilized the theory of Lakoff and Johnson (2003), which categorizes metaphors into three types: structural metaphors, orientational metaphors, and ontological metaphors. The research found 135 data on structural metaphors, 65 data on orientational metaphors, and 280 data on ontological metaphors. The research concluded that ontological metaphors were the most frequently found, while orientational metaphors were the least frequently found.    Keywords: Metaphor, Structural Metaphor, Orientational Metaphor, Ontological Metaphor, Song Lyrics, Taylor Swift